KAJIAN USAHA TANI HUTAN RAKYAT JATI DI DESA LAMBIKU KECAMATAN NAPABALANO (Farming Study Teakâs Community Forest at Lambikuâs Teak Community Forest Farming Study At Lambiku Village Napabalano District) - Salim Mando, La Ode Agus; Midi, La Ode; Hasani, Umar Ode; Setiawan, Agus (MATOA : JURNAL ILMU KEHUTANAN, 2015)
Lambiku Silvan society was relative so long develops farming teak community forest with agroforestry system. But, until currently havent available research that to study about community forest patterns teak and acquired financial gain farmer at silvan that.This research is executed by use of analisis descriptive survey method. Witting prescribed sample to farmer that have plant genus community forest teak. Herein gets to be divided 2 (two) observing category, which is : 1) teak community forest to know people forest patterns and potency dimension in shaped total diamater measure, and tall treed; 2) farmer to know any kind which gets bearing hand in glove with farming activity. Farmer sample take as respondent as bases farm ownership extent. Strata I, its extent is smaller of 1,00 ha; Strata II, 1,00 - 2,00 ha; and Starata III, are even greater of 2,00 ha. Each strata consisting of 10 respondents, so total respondent becomes 30 person.Â Result observationaling to point out that 1) Found 4 (four) pattern plants out teak commnuity forest farming which is : a) Pattern I to cover type: wood, plantation, and perennial; b) Pattern II covers: wood, plantation, perennial and fruit; c) Pattern III to cover type: wood, plantation, and grass; Pattern IV to cover type: wood, plantation, and fruit. 2) nominal gain of teak community forest farming which is: a) Pattern I as big as Rp.Â 666. 066. 182,50, b) patterns II as big as Rp. 642. 246. 423,80; c ) Patterns III as big as Rp. 739. 033. 043,40 and d.) Pattern IV. as big as Rp. 711. 528. 320,65. Each farming pattern teak community forest so reasonable financial ala for contrived because have point as follows: a ) Pattern I: NPV = Rp 57. 920. 525,87, BCR = 2,90, IRR = 14%; b) Pattern II : NPV = Rp. 54.074.191,37, BCR = 2,67, IRR = 14%; c) Pattern III : NPV = Rp. 70.416.104,65, BCR = 3,99, IRR = 14%; d) PatternÂ IV : NPV = Rp. 66.490.033,66, BCR = 3,67, IRR = 14%.Â Â Key words:Â Pattern Farming, Teaks community forest, NPV, BCR, IRR